2011
DOI: 10.1103/physrevlett.106.230403
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Subdiffusion in a Disordered Interacting System

Abstract: We study the transport dynamics of matter-waves in the presence of disorder and nonlinearity. An atomic Bose-Einstein condensate that is localized in a quasiperiodic lattice in the absence of atom-atom interaction shows instead a slow expansion with a subdiffusive behavior when a controlled repulsive interaction is added. The measured features of the subdiffusion are compared to numerical simulations and a heuristic model. The observations confirm the nature of subdiffusion as interaction-assisted hopping betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
154
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(167 citation statements)
references
References 34 publications
13
154
0
Order By: Relevance
“…All the real space experiments were explicitly done for non-interacting particles and, for 3D, in the regime of a very strong disorder potential and/or for very low single-particle energies (in agreement with k dis 1). The inclusion of inter-particle interaction rather leads to a suppression of Anderson localization [28][29][30] and, as demonstrated recently, to sub-diffusive behavior in 1D [31]. In 2D and 3D, however, the understanding is still far from complete, see [32][33][34] and references therein.…”
Section: Anderson Localization -Disorder Vs Interactionmentioning
confidence: 99%
See 3 more Smart Citations
“…All the real space experiments were explicitly done for non-interacting particles and, for 3D, in the regime of a very strong disorder potential and/or for very low single-particle energies (in agreement with k dis 1). The inclusion of inter-particle interaction rather leads to a suppression of Anderson localization [28][29][30] and, as demonstrated recently, to sub-diffusive behavior in 1D [31]. In 2D and 3D, however, the understanding is still far from complete, see [32][33][34] and references therein.…”
Section: Anderson Localization -Disorder Vs Interactionmentioning
confidence: 99%
“…(31) indicated in Chapter 2, and finally apply the contact interaction approximation to eq. (31), that leads to an explicit expression forT (1) U (E 12 ). We again employ units in which h/2m ≡ 1.…”
Section: B1 the Two-body T-matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Anderson himself first noticed the importance of interaction in localization phenomena [8] and launched a theoretical investigation in collaboration with Fleishman [9]. Recently, advances in technology have reinvigorated theoretical [10,11] and experimental [12][13][14][15][16][17][18][19] interest on this subject. For the special case of two interacting particles in a random one-dimensional (1D) potential, Shepelyansky has investigated the interplay of disorder and interaction and concluded that interaction modifies (weakens) localization [20].…”
mentioning
confidence: 99%